2019
DOI: 10.21307/ane-2019-023
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone induces alterations of slow wave oscillation, rapid eye movement sleep and high-voltage spindle in rats

Abstract: Glucocorticoids arising from chronic stress and long-term inflammatory treatment with corticosteroids are both associated with neuropathology and cognitive impairments. Many previous studies have focused on changes in brain morphology and deficits in learning behavior. However, effects of long-term exposure to stress hormones on electrical brain signaling and sleep-wake patterns have remained largely unexplored. This study aimed to monitor electroencephalographic (EEG) patterns induced by prolonged dexamethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Considering the fact that SXT has little effect on cysts as opposed to tachyzoites, the active disseminating form of the parasite, we nonetheless chose to test SXT since Watts et al demonstrated that cysts were in fact active and replicating 36 . On the other hand, we treated mice with Dexamethasone (DXM) seven days in order to access the involvement of inflammation while preventing reactivation of cysts: This length of treatment was reported not to promote sleep‐wake alterations in rats 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the fact that SXT has little effect on cysts as opposed to tachyzoites, the active disseminating form of the parasite, we nonetheless chose to test SXT since Watts et al demonstrated that cysts were in fact active and replicating 36 . On the other hand, we treated mice with Dexamethasone (DXM) seven days in order to access the involvement of inflammation while preventing reactivation of cysts: This length of treatment was reported not to promote sleep‐wake alterations in rats 37 …”
Section: Discussionmentioning
confidence: 99%
“… 36 On the other hand, we treated mice with Dexamethasone (DXM) seven days in order to access the involvement of inflammation while preventing reactivation of cysts: This length of treatment was reported not to promote sleep‐wake alterations in rats. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Demisch et al [ 10 ] showed that acute administration of DXM (1 mg) changed the production of nocturnal melatonin (sleep-wake cycle regulator), indicating that steroid-induced sleep disturbance requires only one dose of DXM induction. In the animal model, an administration of 0.5 mg/kg DXM once daily for 21 consecutive days causes an increase in the power of slow EEG frequencies during wake state and decreases the time spent in REM sleep [ 11 ].…”
Section: Introductionmentioning
confidence: 99%